SLC12A3 Variation and Renal Function in Chinese Patients With Hypertension - Huang, Chin-Chou; Chung, Chia-Min; Yang, Chih-Yu; Leu, Hsin-Bang; Huang, Po-Hsun; Lin, Liang-Yu; Wu, Tao-Cheng; Lin, Shing-Jong; Pan, Wen-Harn; Chen, Jaw-Wen (Frontiers in Medicine, 2022)
Objective: SLC12A3 (solute carrier family 12 member 3) gene variants are associated with diabetic nephropathy; however, their association with hypertensive nephropathy remains unknown. We aimed to investigate the association between SLC12A3 gene polymorphisms and renal function in patients with hypertension. Methods: Participants from three non-diabetic hypertensive cohorts, including young-onset hypertension (cohort 1, n = 882), treatment-naïve hypertension (cohort 2, n = 90), and follow-up cohort (cohort 3, n = 166), underwent genotyping for single nucleotide polymorphisms in SLC12A3. Renal events were defined as a > 25% and > 50% decline in estimated glomerular filtration rate (eGFR). Results: In cohort 1, SLC12A3 rs16963397 C/C or C/G (P = 0.005), rs13334864 C/C or C/T (P = 0.020), and rs7187932 A/A or A/G polymorphisms (P = 0.014) had higher eGFRs compared to their counterparts, with similar findings observed in cohort 2. In cohort 3, over a mean follow-up of 5.8 ± 1.7 years, participants with either SLC12A3 rs16963397 C/C or rs13334864 C/C polymorphisms had more > 25% and > 50% eGFR decline than their counterparts (log-rank test, P = 0.058 and P = 0.038, respectively). Cox regression analysis revealed that SLC12A3 rs16963397 C/C and rs13334864 C/C polymorphisms were significantly associated with an increased risk of > 25% (hazard ratio [HR], 3.294; 95% confidence interval [CI], 1.158–9.368; P = 0.025) and > 50% decline in eGFR (HR, 18.630; 95% CI, 1.529–227.005, P = 0.022) than their counterparts. Conclusion: SLC12A3 polymorphisms are associated with renal function in Chinese patients with hypertension.